De novo CD5+ diffuse large B‐cell lymphoma: Adverse outcomes with and without stem cell transplantation in a large, multicenter, rituximab treated cohort. Issue 4 (June 2016) - Alinari, Lapo; Gru, Alejandro; Quinion, Carl; Huang, Ying; Lozanski, Arletta; Lozanski, Gerard; Poston, Jacqueline; Venkataraman, Girish; Oak, Eunhye; Kreisel, Friederike; Park, Steven I.; Matthews, Stephanie; et al.
Abstract : De novo CD5+ diffuse large B‐cell lymphomas (DLBCL) are a distinct subgroup of DLBCL with poor prognosis. However the role of rituximab‐containing therapy and salvage stem cell transplantation in this patients' population remain to be defined. We retrospectively reviewed clinical features and outcomes of 102 patients with de novo CD5+ DLBCL treated with rituximab‐containing therapy at nine different institutions. By Hans' criteria, 64 patients had activated B‐cell (ABC) subtype, 24 germinal center B‐cell (GCB) subtype, and 14 were not evaluated. No patients had a myc translocation. Eighty‐three patients were treated with rituximab, cyclophosphamide, doxorubicin, vincristine, prednisone (R‐CHOP), 7 with rituximab, etoposide, cyclophosphamide, doxorubicin, vincristine, prednisone (R‐EPOCH), and 6 with R‐CHOP with methotrexate, 3 g/m 2 . The overall response rate to front‐line therapy was 85%. The 3‐year progression free survival (PFS) and overall survival (OS) for all patients were 40 and 65%, respectively. The 3‐year PFS for ABC‐ and GCB‐subtypes was 34 and 45%, respectively. The 3‐year OS for ABC‐ and GCB‐subtypes was 62 and 67%, respectively. The median time to second treatment failure was 3 months and 1 month for ABC‐ and GCB‐subtypes, respectively. Twenty of 28 (71%) transplanted patients with autologous, allogeneic, or both, relapsed. This study confirms the poor prognosis of de novo CD5+ DLBCL in a large multi‐center cohort despite initial rituximab‐containing chemotherapy and suggests that stem cell transplantation fails to salvage the majority of these patients. Approaches to prevent recurrence and/or novel therapies for relapsed disease are needed for this subgroup of DLBCL patients. Am. J. Hematol. 91:395–399, 2016. © 2016 Wiley Periodicals, Inc.